Is Nuclear Anarchy Sustainable? A Temporal Approach - Ye. I. Uchaev; A. A. Kvartalnov (Vestnik MGIMO-Universiteta)
The article develops a novel temporal approach to the sustainability of nuclear anarchy. The extant literature offers two opposite perspectives on the topic: some scholars argue that nuclear anarchy is unsustainable, since it will inevitably either lead to a catastrophic nuclear war or evolve into a hierarchical world order. Their opponents doubt the inevitability of nuclear war in a system of sovereign states and/or its catastrophic nature. However, the debate, as it stands now, ignores the fact that both technology and social structures are embedded in – and mediated by – cultures and worldviews. In particular, both nuclear weapons and interstate anarchy are embedded in specific temporalities.Taking this fact into account, we identify and compare perceptions of time that are interrelated with nuclear weapons, on one hand, and international anarchy, on the other. The article reveals a temporal contradiction of nuclear anarchy: while nuclear weapons imply a potential finitude of humanity, the system of sovereign states is intrinsically connected with an indefinite temporality. We derive two theoretical implications form the concept of temporal contradiction. First, a realization of finite temporality should subvert the legitimacy of an anarchic world order and encourage limitations on national sovereignty. Second, international anarchy should ‘eternalize’ nuclear weapons, i.e., reinterpret them as compatible with the eternity of human civilization. Familiar events of nuclear history including early attempts to establish international control of nuclear energy, the Strategic Defense Initiative, and the evolution of the anti-nuclear movement are interpreted here as empirical evidence in favor of the theoretical implications described above.Thus, the concept of temporal contradiction provides another argument in favor of the idea that nuclear anarchy is unsustainable in the long run, since the proliferation of the finite temporality leads to international hierarchy, whereas persistent indefinite temporality masks the severity of the nuclear threat, making nuclear war more conceivable and probable.